Evaluation of Fibrin-Agarose Tissue-Like Hydrogels Biocompatibility for Tissue Engineering Applications - Campos, Fernando; Bonhome-Espinosa, Ana Belen; Chato-Astrain, Jesús; Sánchez-Porras, David; García-García, Óscar Darío; Carmona, Ramón; López-López, Modesto T.; Alaminos, Miguel; Carriel, Víctor; Rodriguez, Ismael A. (Frontiers in Bioengineering and Biotechnology, 2020)
Generation of biocompatible and biomimetic tissue-like biomaterials is crucial to ensure the success of engineered substitutes in tissue repair. Natural biomaterials able to mimic the structure and composition of native extracellular matrices typically show better results than synthetic biomaterials. The aim of this study was to perform an in vivo time-course biocompatibility analysis of fibrin-agarose tissue-like hydrogels at the histological, imagenological, hematological and biochemical levels. Tissue-like hydrogels were produced by a controlled biofabrication process allowing the generation of biomechanically and structurally stable hydrogels. The hydrogels were implanted subcutaneously in 25 male Wistar rats and evaluated after 1, 5, 9 and 12 weeks of in vivo follow-up. At each period of time, animals were analyzed using magnetic resonance imaging (MRI), hematological analyses and histology of the local area in which the biomaterials were implanted, along with major vital organs (liver, kidney, spleen and regional lymph nodes). MRI results showed no local or distal alterations during the whole study period. Hematology and biochemistry showed some fluctuation in blood cells values and in some biochemical markers over the time. However, these parameters were progressively normalized in the framework of the homeostasis process. Histological, histochemical and ultrastructural analyses showed that implantation of fibrin-agarose scaffolds was followed by a progressive process of cell invasion, synthesis of components of the extracellular matrix (mainly, collagen) and neovascularization. Implanted biomaterials were successfully biodegraded and biointegrated at 12 weeks without any associated histopathological alteration in the implanted zone or distal vital organs. In summary, our in vivo study suggests that fibrin-agarose tissue-like hydrogels could have potential clinical usefulness in engineering applications in terms of biosafety and biocompatibility.